The Small Secreted Protein FoSsp1 Elicits Plant Defenses and Negatively Regulates Pathogenesis in Fusarium oxysporum f. sp. cubense (Foc4) - Yuhua Wang; Xinchun Zhang; Tian Wang; Siyu Zhou; Xiaofei Liang; Changping Xie; Zhensheng Kang; Daipeng Chen; Li Zheng (Frontiers in Plant Science, 2022)
Fusarium wilt of banana (Musa spp.), a typical vascular wilt disease caused by the soil-borne fungus, Fusarium oxysporum f. sp. cubense race 4 (Foc4), seriously threatens banana production worldwide. Pathogens, including vascular wilt fungi, secrete small cysteine-rich proteins during colonization. Some of these proteins are required for pathogenicity. In this study, 106 small secretory proteins that contain a classic N-terminal signal peptide were identified using bioinformatic methods in Foc4. Among them, 11 proteins were selected to show transient expressions in tobacco. Interestingly, transient expression of FoSsp1 in tobacco, an uncharacterized protein (of 145 aa), induced necrotic cell death reactive oxygen burst, and callous deposition. Furthermore, the expression of FoSSP1 in Foc4 wild type (WT) was up-regulated during the stage of banana roots colonization. A split-marker approach was used to knock out FoSSP1 in the Foc4 WT strain. Compared with the WT, the deletion mutant Fossp1 was normal in growth rate but increased in conidiation and virulence. RT-qPCR analysis showed that the expression of four conidiation regulator genes in the Fossp1 deletion mutant was significantly decreased compared to the WT strain. In addition, the expression of four pathogenesis-related genes of bananas infected with Fossp1 deletion mutant was down-regulated in comparison with that of the WT. In summary, these results suggested that FoSSP1 is a putative elicitor that negatively regulates conidiation and pathogenicity in Foc4.